Coronavirus Host Genomics Study: South Africa (COVIGen-SA). (6th October 2022) - May, Andrew K.; Seymour, Heather; Etheredge, Harriet; Maher, Heather; Nunes, Marta C.; Madhi, Shabir A.; Sokhela, Simiso M.; Venter, W. D. Francois; Martinson, Neil; Nabeemeeah, Firdaus; Cohen, Cheryl; Moyes, Jocelyn; et al.
Abstract : Host genetic factors are known to modify the susceptibility, severity, and outcomes of COVID-19 and vary across populations. However, continental Africans are yet to be adequately represented in such studies despite the importance of genetic factors in understanding Africa's response to the pandemic. We describe the development of a research resource for coronavirus host genomics studies in South Africa known as COVIGen-SA—a multicollaborator strategic partnership designed to provide harmonised demographic, clinical, and genetic information specific to Black South Africans with COVID-19. Over 2, 000 participants have been recruited to date. Preliminary results on 1, 354 SARS-CoV-2 positive participants from four participating studies showed that 64.7% were female, 333 had severe disease, and 329 were people living with HIV. Through this resource, we aim to provide insights into host genetic factors relevant to African-ancestry populations, using both genome-wide association testing and targeted sequencing of important genomic loci. This project will promote and enhance partnerships, build skills, and develop resources needed to address the COVID-19 burden and associated risk factors in South African communities.